Performance assessment in strength and conditioning - Jones, Paul A.; McMahon, John J.; Nelson, Lee (Routledge, Taylor & Francis Group, 2019)
It is an essential skill for any strength and conditioning coach to be able to reliably assess the physical performance of their athletes and communicate the results and their implications to performers and coaches, alike. The book explores the full range of considerations required to reliably assess performance, including questions of ethics and safety, reliability and validity, and standardised testing, before going on to recommend (through a comparison of field- and laboratory-based techniques) the optimal methods for testing all aspects of physical performance.